PEMODELAN MATEMATIKA ALIRAN UDARA PADA PARU-PARU AKIBAT PENYAKIT CORONAVIRUS DISEASE 2019 (COVID-19) - Setiawan, Yogi - (Kadikma, 2021)
The bronchial airways are an important part of the respiratory system, it is not uncommon for the bronchi to experience disturbances, one of the disorders due to coronavirus diseases (Covid-19). Coronavirus diseases (Covid-19) are what cause narrowing of the bronchial tubes so that they will interfere with the speed of air flow. This airflow speed will be modeled with mathematical language. The mathematical model of air flow velocity in this study is formed based on equations of momentum equations which are then solved by the finite element method. Speed ​​analysis Air flow was simulated using MATLAB and FLUENT software. The problems studied are the effect of the narrowing diameter, initial velocity, and viscosity on the air flow velocity. Based on the research results show that the smaller the narrowing diameter and the viscosity of the incoming air, the greater the airflow velocity, while for the greater the initial velocity, the greater the resulting airflow velocity. Keywords: Coronavirus Diseases 2019 (Covid-19), bronchial, lungs, airways, finite element method.